PENGARUH KUALITAS PELAYANAN, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMAKAIAN JASA TRAVEL UMROH DAN HAJI PT. ALIFAH TOUR CABANG BOGOR - Toni Endaryono, Bakti; Ekawati, Christina (Jurnal Gici Jurnal Keuangan dan Bisnis, 2023)
Along with the development of the travel business today is getting tighter. This is felt by business people in the field of Umrah and Hajj travel services. PT. Alifah Tour Bogor Branch is one of the companies engaged in Umrah and Hajj travel services. PT. Alifah Tour Bogor Branch is one of the companies engaged in Umrah and Hajj travel services. This study aims to analyze how much influence the quality of service, price and promotion on the decision to use Umrah and Haji travel services of PT. Alifah Tour Bogor Branch. Where the decision variable of service usage (Y), service quality variable (X1), price variable (X2), and promotion (X3). Hypothesis testing using tests shows that partial service quality and price have a significant effect. While the promotion variable does not have a significant effect on the decision to use Alifah Tour Bogor Branch Travel services. Then through test F it can be seen that the three independent variables studied, namely service quality, price and promotion simultaneously have a significant effect on the decision to use Umrah and Hajj travel services of PT. Alifah Tour Bogor Branch. The adjusted R Square figure of 0.556 shows that 55.6% of service usage decision variables are explained and influenced by service quality, price and promotion and the remaining 44.4% is explained and influenced by other variables not explained in this study. Keywords: Service Quality, Price, Promotion, Usage Decision.